2006
DOI: 10.1007/s11296-006-0028-7
|View full text |Cite
|
Sign up to set email alerts
|

Train the trainers!

Abstract: With the introduction of training programmes and logbooks for basic postgraduate training and subspecialty training, the European Board and College of Obstetrics and Gynaecology has given impulses to harmonise training in obstetrics and gynecology in the European Union. Current changes in the practice of medicine, among which the European Working Time Directive, numbers of surgical procedures decreasing, more demanding patients and a change in work ethos, challenge both trainers and trainees to optimise postgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…concluded that, ‘surgical teams would welcome a structured tool to facilitate debriefing at the end of every case’. However, it is not unusual to find discordance between faculty and trainees with reported perceptions on the quality of feedback . In a focus group study interviewing trainees and faculty, van der Houwen et al .…”
Section: Discussionmentioning
confidence: 99%
“…concluded that, ‘surgical teams would welcome a structured tool to facilitate debriefing at the end of every case’. However, it is not unusual to find discordance between faculty and trainees with reported perceptions on the quality of feedback . In a focus group study interviewing trainees and faculty, van der Houwen et al .…”
Section: Discussionmentioning
confidence: 99%
“…In order to better adapt to this new training culture and framework, surgical supervisors themselves need to up‐skill in areas of trainee management and assessment. There have been many ‘train the trainer’ courses in medicine implemented in Australia and abroad 14–16 . It is felt that in order to correctly perform in‐training assessment of competence in trainee surgeons, surgical trainers themselves need to achieve competence through attending courses designed for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…There have been many 'train the trainer' courses in medicine implemented in Australia and abroad. [14][15][16] It is felt that in order to correctly perform in-training assessment of competence in trainee surgeons, surgical trainers themselves need to achieve competence through attending courses designed for this purpose. In a commentary by Wiess in Family Medicine, 2004 the point was made that many medical educators don't know how to distinguish between a good trainee and an average one and that they themselves may not be competent enough to reliably deem a trainee competent without structured reference tools.…”
Section: It Should Be Run On a Regular Basis With Invitation To Fellomentioning
confidence: 99%